2018
DOI: 10.3390/rs10010077
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Land Cover Mapping through Integration of Pixel-Based and Object-Based Classifications from Remotely Sensed Imagery

Abstract: Abstract:Pixel-based and object-based classifications are two commonly used approaches in extracting land cover information from remote sensing images. However, they each have their own inherent merits and limitations. This study, therefore, proposes a new classification method through the integration of pixel-based and object-based classifications (IPOC). Firstly, it employs pixel-based soft classification to obtain the class proportions of pixels to characterize the land cover details from pixel-scale proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 49 publications
0
17
0
2
Order By: Relevance
“…GFSAD30 and GlobeLand30, which have shown better cropland estimation in Western Sahel, compared to the other land cover products, were developed using random forest and pixel-object-based (i.e., an optimization of the pixel-based and object-based methods) classification algorithms, respectively. These new algorithms are becoming popular within the remote sensing community, because of their abilities to accurately classify land cover [26,27]. However, at the country and regional scales of this West Africa analysis, using high quality and high density reference information, we found that both GFSAD30 and GlobeLand30 have a cropland class user's accuracy below that reported by the producers; which is in conformity with previous findings in assessing the GlobeLand30 dataset at a country level (Kenya) reported by the authors of [28].…”
Section: Discussionmentioning
confidence: 99%
“…GFSAD30 and GlobeLand30, which have shown better cropland estimation in Western Sahel, compared to the other land cover products, were developed using random forest and pixel-object-based (i.e., an optimization of the pixel-based and object-based methods) classification algorithms, respectively. These new algorithms are becoming popular within the remote sensing community, because of their abilities to accurately classify land cover [26,27]. However, at the country and regional scales of this West Africa analysis, using high quality and high density reference information, we found that both GFSAD30 and GlobeLand30 have a cropland class user's accuracy below that reported by the producers; which is in conformity with previous findings in assessing the GlobeLand30 dataset at a country level (Kenya) reported by the authors of [28].…”
Section: Discussionmentioning
confidence: 99%
“…More important, the accuracy of our results was relatively high. We attributed this high accuracy to the fact that OBIA not only uses spectral features of ground objects but also uses spatial features and textures, spatial structure features, shape, and other characteristics [1,10]. Thus, to a large extent, OBIA can overcome the negative effects of metameric substances with the same spectrum and a metameric spectrum with the same substance caused by using only spectrum features in traditional pixel-based methods to improve classification accuracy [11,12,22].…”
Section: Issues For Obiamentioning
confidence: 99%
“…Experimental results show that the proposed SRMSAM-PAN can obtain a higher mapping accuracy than the existing SRMSAM methods.In recent years, many studies on SRM have been rapid developed. The Hopfield neural network [6,7], back-propagation neural network [8,9], object spatial dependence [10,11], indicator cokriging (ICK) [12,13], point spread function [14,15], and some super-resolution methods [16][17][18] have been successfully utilized in SRM. The above methods belong to soft-then-hard super-resolution mapping (STHSRM) types.…”
mentioning
confidence: 99%